Future space missions and human enhancement: Medical and ethical challenges. (October 2021) - Szocik, Konrad; Shelhamer, Mark; Braddock, Martin; Cucinotta, Francis A.; Impey, Chris; Worden, Pete; Peters, Ted; Ćirković, Milan M.; Smith, Kelly C.; Tachibana, Koji; Reiss, Michael J.; Norman, Ziba; et al.
Highlights: Human enhancement for future space missions is a reasonable option. Different methods of human enhancement for space include gene editing or implants. Ethics should support a careful application of human enhancement for space missions. Abstract: Future human space missions to Mars and beyond may be realized for different research, economic, political or survival reasons. Since space remains a hazardous environment for humans, space exploration and exploitation requires the development and deployment of effective countermeasures. In this paper, we discuss prospects for human enhancement by gene editing, synthetic biology, or implants, for the purposes of future space missions. We argue that there are good reasons to consider such options, and that ethical arguments can be made in favor of human enhancement to enable long-term space exploration.